Process of informal occupation of the territory and its influence on the historical landscape - cultural case: Cerro Intiorko, high district of the alliance, city of Tacna 2003 to 2017 - Medina Bejar, Keily Norka (2020)
The city of Tacna presents a historical cultural landscape, which comes from the war with Chile of 1879, leaving as a footprint the Crypt of the Heroes, high in the Intiorko Hill, in front of the city, in search of paying homage to the fallen In the Field of the Alliance, from 1901, with the accomplishment of different protocol ceremonies that counted on the participation of all the population tacneña fervent patriot, until the year of 1979. The present investigation aims to determine the influuence of the process of Informal occupation of the territory in the historical cultural landscape of the hill Intiorko, in the district of Alto de la Alianza, in the city of Tacna. The research focused its methodology, under a quantitative approach, basic type, non - experimental design, with a descriptive - explanatory hypothesis, applying the statistics. The questionnaire was applied as a measurement instrument; Which allowed to gather information, relate and measure study variables and their dimensions. The study sample consisted of the 359 plots of the livestock associations of the study area; The variables contribute to the evaluation of the landscape, based on its analysis from the visual approach, based on the guidelines established by Spanish regulations. The obtained results allowed to establish that: the informal occupation of the territory influuences in the alteration of the landscape, in the diminution of its visual quality, based on the evaluation of the visualized landscape; Due to the reduction of the natural area with respect to the area occupied by the anthropic activity, with the risk of occupying the space corresponding to the Crypt of the Heroes, that is why a territorial planning that allows the growth of the city in an ordered way, Sustainable in the medium and long term is of utmost importance for the development of a city.